1985
DOI: 10.1080/03768358508439152
|View full text |Cite
|
Sign up to set email alerts
|

Education and development in the South African context

Abstract: In line with international experience it is now widely accepted in South Africa that education has an important role to play in development, particularly of socio-economically disadvantaged communities, although there is less certainty now than in the sixties as to what that role is. It cannot be governed solely by the manpower needs of the economy: men and women have their own equally important needs. Nor can this role be effective as long as education is equated with formal schooling, particularly where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Education policy can be considered as an action by the government, through legislation, that the implementation of any policy should hold benefits for a country and its citizens (Hartshorne, 1999). Considering the aforementioned view, indications such as "action" and "hold benefits" (Hartshorne, 1999) call for the implementation of possible policy options.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Education policy can be considered as an action by the government, through legislation, that the implementation of any policy should hold benefits for a country and its citizens (Hartshorne, 1999). Considering the aforementioned view, indications such as "action" and "hold benefits" (Hartshorne, 1999) call for the implementation of possible policy options.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education policy can be considered as an action by the government, through legislation, that the implementation of any policy should hold benefits for a country and its citizens (Hartshorne, 1999). Considering the aforementioned view, indications such as "action" and "hold benefits" (Hartshorne, 1999) call for the implementation of possible policy options. In the case of this paper, possible policy options regarding innovative capabilities were identified that can be applied by HEIs to equip pre-service teachers with capabilities to enact SJL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The economic growth model used in this research is based, with little alteration, on the neoclassical Solow production function. According to Romer's definition, economic growth is a function of capital accumulation, an extension of labour-power and an "exogenous" factor, technological advancement which makes physical capital and labor more productive (Mankiw, Romer and Weil, 1992), Hartshorne (1985) as quoted in Saad and KalaKech (2009), Romer (1996) as quoted in Novignon et al (2012), andOdusola (2002). …………………………………….. 2The linearized equation for the above will appear as:…”
Section: Analytical Framework Of the Modelmentioning
confidence: 99%
“…Some 20 years after the end of apartheid, and despite the government’s progressive rhetoric, the promise of empowerment and emancipation has not materialized for the majority of South Africans, who continue to bear the burden of poor education. A number of reasons have been suggested for this failure in education delivery, including high student–teacher ratios, poorly trained teachers, gaps between policy and practice, a lack of resources needed to implement the necessary changes, government bureaucracy underplaying or overlooking the realities on the ground in South African schools, and a bias toward political symbolism (Hartshorne, 1999; Jansen, 2002; Kahn, 1996; Kallaway, 2002; Manganyi, 2001; Maodzwa-Taruvinga & Cross, 2012). But it is paradoxical that a country with the wealthiest economy on the continent has a schooling system that is among the poorest performing systems in the world, ranking 140th out of 144 countries (Patel, 2012).…”
Section: Education Link To Inequalitymentioning
confidence: 99%